Effect of film-like retained austenite on low temperature toughness of high strength offshore steel. (2nd October 2019) - Zhang, Xiangyun; Li, Jiguang; Yan, Ling; He, Xuze
Abstract: Film-like retained austenite was prepared by a quenching + intercritical annealing + tempering (QIAT) heat treatment to study its effect on the low temperature toughness of high strength offshore steel. Based on the Purdy model, the flat growth mechanism of film-like retained austenite was studied and the toughening mechanism of this kind of retained austenite was revealed. The results showed that the microstructure after the QIAT heat treatment was a multi-phase structure containing tempered bainite/martensite, intercritical ferrite and film-like retained austenite. The thickness of the film-like retained austenite was only 0.1 μ m. The yield strength was 716 MPa, the tensile strength was 812 MPa and the low temperature toughness at −40 °C reached 150 J. The low temperature toughness was significantly improved compared with the quenching + tempering (QT) treatment. Enrichment of Mn in the retained austenite formation region caused a surge in dissipated free energy induced by austenite interface migration, making it a one-dimensional film-like flat growth. The excellent stability of the film-like retained austenite and the large number of low-angle grain boundaries were the reasons for the excellent low temperature toughness of this offshore steel.